Plasma proteomic analysis reveals altered protein abundances in HIV‐infected patients with or without non‐Hodgkin lymphoma. Issue 8 (26th April 2022) - Zhuang, Ke; Zhang, Yongxi; Mo, Pingzheng; Deng, Liping; Jiang, Yong; Yu, Lei; Mei, Fanghua; Huang, Shaoxin; Chen, Xi; Yan, Yajun; Tang, Hongbin; Li, Xiangdong; et al.
Abstract: The identification of circulating proteins associated with acquired immunodeficiency syndrome‐related non‐Hodgkin lymphoma (AIDS‐NHL) may help in the development of promising biomarkers for screening, diagnosis, treatment, and prognosis. Here, we used quantitative liquid chromatography‐tandem mass spectrometry (LC–MS/MS) to identify differentially expressed proteins (DEPs) in plasma collected from patients with AIDS‐NHL and human immunodeficiency virus (HIV)‐infected patients without NHL (HIV + ). Proteins with a log2 (fold change) in abundance >0.26 and p  < 0.05 were considered differentially abundant. In total, 84 DEPs were identified, among which 20 were further validated as potential biomarkers, with immunoglobulin and complement components being the most common proteins. Some of the proteins were further verified in a retrospective analysis of the medical records of patients in a larger cohort. These markedly altered proteins were found to mediate pathophysiological pathways that likely contribute to AIDS‐NHL pathogenesis, such as the humoral immune response, complement activation, and complement and coagulation cascades. Our findings provide a new molecular understanding of AIDS‐NHL pathogenesis and provide new evidence supporting the identification of these proteins as possible biomarkers in AIDS‐NHL.